Pembentukan Karakter Religius Santri Madrasah Diniyah: Studi Kasus di Madrasah Diniyah Miftakhul Ulum Gambirkuning Kraton Pasuruan - Lutfi, Muhammad Khoirul (Tarbawi : Jurnal Studi Pendidikan Islami, 2022)
For some people to criticize educational institutions. Various worrying phenomena are currently appearing in mass media, including television, newspapers, etc. These phenomena include fights between students, promiscuity, drug cases among students, and students celebrating graduation with drinking parties. This research focuses on: What are the efforts of Madrasah Diniyah Miftakhul Ulum Gambirkuning Kraton teachers in forming the religious character of students? And the inhibiting and supporting factors for the efforts of Madrasah Diniyah Miftakhul Ulum Gambirkuning Kraton teachers in forming the religious character of students. This research is field research with a qualitative type of research. In this qualitative research, the data collected takes the form of words or images rather than numbers. data obtained directly from the research object, namely from interviews with Madrasah Principals, Teachers, TU and student guardians. Learning activities are the core activities in forming the religious character of students. Learning activities at Madrasah Diniyah Miftakhul Ulum all contain subjects based on Islamic knowledge such as Tauhid, Akhlak, Jurisprudence, Arabic, Al-Qur'an, Hadith, Nahwu, Shorof, Tafsir, Faroid, Falak Science, Tareh Nabi, Imlak and how to quickly read the yellow book using the Al-Miftakh method. With these subjects, students receive lessons that directly provide religious knowledge and values ​​to form students with a religious character.